Pharmaceutical calculations - Ansel, Howard C. (Philadelphia, Pennsylvania : Lippincott Williams & Wilkins, 2010)
Represents a thorough update of this textbook, which for more than six decades has met the needs of students in this important subject area.
Fundamentals of pharmaceutical calculations -- International system of units -- Pharmaceutical measurement -- Interpretation of prescriptions and medication orders -- Density, specific gravity, and specific volume -- Percentage, ratio strength, and other expressions of concentration -- Calculation of doses: general considerations -- Calculation of doses: patient parameters -- Some calculations involving "units',"... -- Selected clinical calculations -- Isotonic and buffer solutions -- Electrolyte solutions: milliequivalents, millimoles, and miliosmoles -- Intravenous infusions, parental admixtures, and rate-of-flow calculations -- Enteral and parenteral nutrition, body mass index, and the food nutrition label -- Altering product strength, use of stock solutions, and problem-solving by alligation -- Reducing and enlarging formulas -- Selected calculations in contemporary compounding -- Selected calculations involving veterinary pharmaceuticals -- Selected calculations associated with plant extractives -- Calculation of active drug moiety -- Selected calculations involving radiopharmaceuticals -- Selected bioavailability and pharmacokinetic calculations -- Selected pharmacoeconomic calculations
Includes bibliographical references and index.
Keywords: PHARMACEUTICAL ARITHMETIC